Jaga Sungai, Jaga Kehidupan: Integrasi Edukasi Lingkungan, Pengelolaan Sampah dan Aksi Bersih Sungai di Desa Klambir V Kebun - Hidayat, Wahyu; Suranto, Suranto (Universitas Nahdlatul Ulama Sumatera Utara, 2025)
The problem of household waste management remains a significant environmental issue in rural areas, including in Klambir V Kebun Village, Hamparan Perak District, Deli Serdang Regency. The low level of public understanding regarding waste sorting and the habit of throwing waste into drains and rivers has the potential to cause environmental pollution and health problems. This Community Service Program aims to increase public understanding and awareness of proper waste management through the separation of organic and inorganic waste, the utilization of organic waste using the Black Soldier Fly (BSF) composting method, and the strengthening of environmental awareness through river clean-up activities. The implementation method uses a participatory approach through outreach, lectures, discussions, and hands-on practice involving the community and village officials. The materials presented cover types of waste, household waste management, and the application of the BSF composting method. The river clean-up activities serve as a concrete implementation of efforts to maintain environmental quality. The results demonstrate increased public understanding of waste management and awareness of the importance of maintaining river cleanliness. This program contributes to encouraging behavioral change toward more responsible and sustainable environmental management.